SERTIFIKASI HALAL SEBAGAI PENERAPAN ETIKA BISNIS ISLAMI DALAM UPAYA PERLINDUNGAN BAGI KONSUMEN MUSLIM - Ramlan Ramlan; Nahrowi Nahrowi (Universitas Islam Negeri Jakarta, 2014)
Halâl Certification as an Application of Islamic Business Ethics in Muslim Consumer Protection Halâl certification in food is needed by Muslim consumers to provide assurances that they are not consuming or using product or service that are not halâl so that no sin is commited. It is the duty of government to provide assurances to Muslim consumers that consumer goods or services that are circulating amongst society are really halâl. The halâl label itself provides benefits to businesses such as improving consumer confidence to consume, reaching the global halâl food market, increasing the marketability of products in market and low cost investment. Muslim consumers also have to be smart before purchasing product or services for security and safety.DOI: 10.15408/ajis.v14i1.1251